Statistical Analysis of Occupational Accidents Occurring in the Health Sector in Türkiye: Retrospective Cohort Study - Ali Ağar (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The aim of this research is to statistically examine the occupational accidents that occur in the health sector, which has a significant labor force in Turkey, and the results of these accidents. The research aims to determine the accident incidence rate, accident frequency rate and fatal accident frequency rate of healthcare workers and to analyze the relationship between the level of occupational accidents of healthcare workers and the level of occupational accidents of workers in other sectors in Turkey. Method: Data were obtained from the statistical database of the Social Security Institution for the years 2013-2021. Accident incidence rate, accident frequency rate and fatal accident frequency rate are used in the analysis. In addition, the relationships between the insured working in all sectors in Turkey and the insured working in the health sector are examined by correlation analysis with the JAMOVI program. Results: A positive, very strong and significant relationship (r=0.90, p<0.001) was found between the number of insured people who had occupational accidents in Turkey and the number of insured people who had occupational accidents in the health sector. In the health sector between 2013-2021, the accident incidence rate is 1658.6 for every 100,000 employees, the accident frequency rate is 6.9 for every 1,000,000 work hours and the fatal accident frequency rate is 0.06 for every 1,000,000 employees. Conclusion: Although the risks of occupational accidents to which health workers are exposed are lower than in other sectors, there is no significant difference in fatal accidents and cases of permanent incapacity benefits.